Perancangan Jaringan Syaraf Tiruan Umpan Balik Berbasis Windows: Studi Kasus Pengenalan Numerik Arab - Samuel Lukas; Arnold Aribowo; Sepreni Sepreni (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
Artificial Neural Networks are basically software applications that need to beprogrammed. Like any other application, an ANN can be programmed with a programminglanguage, a tool, or both. This paper discussed an analysis how an ANN based on backpropagation learning algorithm can be constructed by using Visual Basic language.Moreover this paper also discusses how we can make an ANN system to identify handwritingof nine numerical Arabic characters.Keywords: artificial neural networks, programming language, nine numerical arabiccharacters.